Hemophilia throughout the life cycle - Catelli, Dayenne Helena; Tabares Calvache, Ebellins; Plentz Portich , Julia; Seganfredo Weber , Cristiane; Sander Hoffmann , Daniel; Rasia Bosi , Guilherme; Sekine, Leo; Mariano da Rocha Silla , Lucia (Clinical and Biomedical Research, 2023)
Hemophilia is an inherited X-linked coagulopathy defined by a deficiency or abnormality in the clotting function of factor VIII (hemophilia A) or factor IX (hemophilia B). The continuous improvement of the treatment has made it possible to monitor the patient through their life cycle with the inherent transition of care, initially by caregivers in childhood and later by the patient himself. Alterations associated with age added to chronic diseases are a constant challenge in the comprehensive treatment of the patient. The inhibitors are IgG alloantibodies directed to exogenous clotting factors, factor VIII or factor IX. The likelihood of developing inhibitors varies from one person with hemophilia to another and depends on the interaction between multiple genetic and environmental factors. This review offers a better understanding of the physiological alterations that allow a comprehensive assessment of the patient with hemophilia.